Anxiety Reflected In Gillian Flynn's Dark Places (2009):A Psychoanalytic Perspective - Trijayanti, Whenny, Dr. M. Thoyibi, M.S (2017)
This research aims to identify the indicators of anxiety in the novel, to find out the dominant type of anxiety in dominant in the novel, to describe how anxiety is reflected in the novel, and to reveal the reasons why Gillian Flynn addresses anxiety in the novel. The type of this research is descriptive qualitative. The researcher gets the data from the novel includes the sentences, and paragraph. The techniques of collecting the data are reading the data repeatedly, taking notes, underlying the important words, arranging the data, selecting the data, and drawing conclusion. The technique of data analysis is descriptive qualitative which comprises three procedures, namely: data reduction, data display, and conclusion. The results of this research show: the indicators of anxiety consist cognitive anxiety, motoric anxiety, somatic anxiety, and affective anxiety. The anxiety reflected in the "Dark Places" novel consists of neurotic anxiety, moral anxiety and realistic anxiety. The type of anxiety that is dominant in the "Dark Place" novel is realistic anxiety. Gillian Flynn address anxiety in the "Dark Places" novel where based on the indicator of anxiety, Gillian wants to address anxiety by showing how the anxiety appears. Based on motoric reaction, body movement visually, such as; shrugged (shows a simple shoulder shrug), become a sensitive person and becomes aware on something, paced around to release muscular tension or discomfort, and bristled and tensed body. The somatic anxiety and affective anxiety is that Libby really anxious about the investigation of her family murder.